Kate's giants - Gregory, Valiska (London : Walker Books, 1995)
Kate doesn't like the attic door in her room. Scary things might come through it, she thinks. There might be wild animals or giants. . . and, lying in the dark, she's sure there are!
Keywords: Fear-Stories; Children's stories